2003
DOI: 10.1074/jbc.m205689200
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Spermidine/SpermineN1-Acetyltransferase Mutant L156F That Decreases Cellular Sensitivity to the Polyamine AnalogueN1,N11-Bis(ethyl)norspermine

Abstract: Properties of a mutant form of spermidine/spermine N 1 -acetyltransferase, L156F (L156F-SSAT), that is present in Chinese hamster ovary cells selected for resistance to the polyamine analogue N 1, N 11 -bis(ethyl)norspermine (BE 3-3-3) were investigated. Increased K m values, decreased V max values, and decreased k cat values with both polyamine substrates, spermidine and spermine, indicated that L156F-SSAT is an inferior and less efficient acetyltransferase than wild-type SSAT. Transfection of L156F-SSAT into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The mutant CHO cells were found to contain a point mutation in the SSAT gene that alters the coding sequence, changing Leu 156 to Phe. This mutation not only greatly impairs the activity but also prevents BE-3-3-3 from protecting the mutant protein from polyubiquitination and degradation (97). Subsequent determination of the crystal structure of SSAT explains these results, since the L156F mutation would change the binding surface for the aliphatic carbons of the substrate/inducer at positions 8 -10 (15).…”
Section: Induction Of Ssatmentioning
confidence: 92%
See 1 more Smart Citation
“…The mutant CHO cells were found to contain a point mutation in the SSAT gene that alters the coding sequence, changing Leu 156 to Phe. This mutation not only greatly impairs the activity but also prevents BE-3-3-3 from protecting the mutant protein from polyubiquitination and degradation (97). Subsequent determination of the crystal structure of SSAT explains these results, since the L156F mutation would change the binding surface for the aliphatic carbons of the substrate/inducer at positions 8 -10 (15).…”
Section: Induction Of Ssatmentioning
confidence: 92%
“…Such binding prevents the formation of polyubiquitinated SSAT (Fig. 4E) (15,35,97). This stabilization causes a large amplification of the effect provided by increased mRNA production and translation in response to the signal of polyamines or analogs.…”
Section: Regulation Of Ssat Content and Effects Of Polyamines And Anamentioning
confidence: 97%
“…In the second, McCloskey and Pegg (2000) found that a point mutation in SSAT gene was responsible for resistance to DENSPM in a Chinese hamster ovary cell line. It was subsequently shown that the analog was unable to effectively sustain high levels of SSAT because of its inability to prevent the ubiquitination and rapid turnover of the mutant SSAT protein (McCloskey and Pegg, 2003). Taking an alternative tack, Vujcic et al (2000) showed that conditional overexpression of SSAT in MCF-7 cells gave rise to a steady depletion of Spd and Spm pools and a gradual inhibition of cell growth.…”
mentioning
confidence: 99%
“…It is likely that the well-studied, post-translational regulatory abilities of BENSpm on the SSAT protein, e.g., enzyme stabilization, are more effective than those of PG-11047, thereby accounting for the more dramatic increase in enzyme activity (42, 46). These results also suggest that the main contribution of MS-275 in the observed SSAT induction is at the level of enhanced transcription.…”
Section: Resultsmentioning
confidence: 99%